An 8500-year palynological record of vegetation, climate change and human activity in the Bosten Lake region of Northwest China - Tarasov, Pavel E.; Demske, Dieter; Leipe, Christian; Long, Tengwen; Müller, Stefanie; Hoelzmann, Philipp; Wagner, Mayke (Elsevier, 2019)
Palynological dataset for the XBWu-46 sediment core extracted from Bosten Lake at the south-eastern end of the Tian Shan, Northwest China, contains a climate record divided into three major intervals: a period of increasing aridity (ca. 8540–4000 cal. yr BP), a peak arid phase (ca. 4000 to 2000/1500 cal. yr BP), and an interval of increasing humidity towards the core top (ca. 60 cal. yr BP). Correlation with other climate proxies from different regions implies that hydrological conditions in Northwest China were governed by Asian summer monsoon precipitation during the early and middle Holocene and that the increase in humidity over the last two millennia was controlled by westerly-derived precipitation. Regional evidence for early human activities in the lake sediments starts to accumulate from the onset of the driest interval comprising records of enhanced charred grass fragment concentrations (since ca. 4350 cal. yr BP), and pollen of Cerealia type (since ca. 4000 cal. yr BP), Xanthium (since ca. 3700 cal. yr BP), and Cannabis type (since ca. 2500 cal. yr BP). These signals are likely related to early agro-pastoral populations of regional Andronovo Culture that, according to archaeological data, appeared in the south-eastern Tian Shan around 4000 cal. yr BP. In addition, increased Xanthium pollen and charred grass fragment abundances point to enhanced human impact linked to intensified Silk Road activities during the Han dynasty (206 BCE–220 CE).